Analisis Sandi Diferensial terhadap AES, DES dan AE1 - Yusuf Kurniawan; Adang Suwandi Ahmad; M. Sukrisno Mardiyanto; Iping Supriana; Sarwono Sutikno (Institute for Research and Community Services (LPPM) ITB, 2006)
Since 1977, DES officially became America encryption algorithm. And then this algorithm spreads over the world to be used in banking, financial industries, and economics. Because of the short of the key, in 2001, DES is replaced by AES. One of the most important problem in cryptology is how to prove the security of algorithm against cryptanalysis. In this paper, we will discuss differential attack to examine the security of DES, AES and AE1. AE1 is block cipher that we proposed. Although differential attack has been proposed since 1990, all of cryptographers in the world still use it to examine the strength of ciphers till now. Our contribution is providing a proof that AE1 can be resistant to differential attack and that our cipher is more secure than DES and AES against differential attack. Unfortunately, our cipher is slower than DES or AES.